Popularizing Newly Released Rice Variety in Jammu by Front Line Demonstrations - Saha, Anuradha; Singh, Bikram; Bharti, Vijay (Indian Farming, 2015)
Rice is the most important kharif crop in irrigated area of Jammu. The stagnation of grain yield of rice indicated that non adoption of improved variety gives lower productivity. The Front Line Demonstrations involving improved rice variety were conducted in different villages during kharif 2011, 2012 and 2013 in order to validate the yield potential of recently released rice variety at farmer’s field and to create awareness among the farmers about the variety. The farmers were highly satisfied with the performance of improved rice variety in terms of higher yield, resistance to diseases compared to local varieties. The economic analysis of demonstration indicated the economic viability of improved variety.